(untitled) (Bangladesh Journal of Microbiology, 2012)
The purpose of the present study is to examine the antibacterial and cytotoxic properties of methanol extract of leaves of Stephania japonica. The crude methanolic extract of S. japonica, n-hexane, chloroform and ethyl acetate soluble fractions of methanolic extract were screened for their antimicrobial activity against a wide range of both Gram-positive and Gram-negative bacteria by disc diffusion method. The crude extract showed moderate and n-Hexane, chloroform soluble fraction of crude extract showed mild antibacterial activity against both Gram-positive and Gram-negative bacteria. Ethyl acetate soluble fraction of the extract showed significant antimicrobial activity against Salmonella typhi, Escherichia coli and Bacillus cereus. The zones of inhibition produced by the crude methanolic extract, n-hexane, chloroform and ethyl acetate soluble fractions were found to be 12.80-16.55 mm, 12.60 mm, 5-14.30 mm and 10-20.25 mm, respectively, at a concentration of 30 g/disc. Chloroform, n-hexane and ethyl acetate soluble fractions of methanolic extract of S. japonica were screened for antitumor properties using brine shrimp lethality bioassay. A reputed cytotoxic agent vincristine sulphate was used as a positive control. From the results of the brine shrimp lethality bioassay, it can be well predicted that chloroform and ethyl acetate soluble fractions of methanolic extract of S. japonica possess cytotoxic principles (with LC50 66.488 mg/ml and LC50 45.662 mg/ml, respectively) comparison with positive control vincristine sulphate (with LC50 0.839 mg/ml). But n-hexane soluble fractions of methanolic extract of S. japonica exhibited no lethality effect on shrimp nauplii. DOI: http://dx.doi.org/10.3329/bjm.v28i2.11816 Bangladesh J Microbiol, Volume 28, Number 2, December 2011, pp 52-56